ACCOUNTABILITY OF VILLAGE FUND ALLOCATION MANAGEMENT IN WINDUROJO VILLAGE, KESESI DISTRICT, PEKALONGAN - Jaelani, Achmad; Kurniawan, Rachmad Risqy; Sari, Hastuti Indra (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2024)
ABSTRACTThis study aims to evaluate the accountability of Village Fund Allocation (VFA) management in Windurojo Village, especially in the planning, implementation, and accountability phase, according to Pekalongan Regent Regulation No. 119 of 2022.  The research method used is qualitative with a descriptive type of research. Data collection is done through interviews, observations, and documentation using descriptive data analysis. The descriptive approach explains how the village government allocates funds in Windurojo Village. The research was conducted at Windurojo Village Hall. Findings from the study show that Windurojo Village has run the planning, implementation, and accountability process of Village Fund Allocation (VFA) can be held accountable. VFA planning is based on program proposals from hamlets evacuated through village development planning deliberations (musrembangdes). The procedure for disbursing and dispensing VFA is appropriate with applicable regulations. With a VFA Fund allocation that is based on a priority scale. The VFA implementation accountability report has been in integrity with APBDEs accountability.ABSTRAKPenelitian ini bertujuan untuk mengevaluasi akuntabilitas pengelolaan Alokasi Dana Desa (VFA) di Desa Windurojo khususnya pada tahap perencanaan, pelaksanaan, dan pertanggungjawaban menurut Peraturan Bupati Pekalongan Nomor 119 Tahun 2022. Metode penelitian yang digunakan adalah kualitatif dengan jenis penelitian deskriptif. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi dengan analisis data menggunakan pendekatan deskriptif. Pendekatan deskriptif menjelaskan tentang bagaimana pemerintah desa mengalokasikan dana desa di Desa Windurojo. Penelitian dilakukan di Balai Desa Windurojo. Hasil penelitian menunjukkan bahwa Desa Windurojo telah menjalankan proses perencanaan, pelaksanaan, dan pertanggungjawaban Alokasi Dana Desa (VFA) dapat dipertanggungjawabkan. Perencanaan VFA didasarkan pada usulan program dari dusun-dusun dan disalurkan melalui musrembangdes. Tata cara pencairan dan penyaluran VFA sesuai dengan ketentuan yang berlaku. Dengan alokasi Dana VFA yang didasarkan pada skala prioritas. Laporan pertanggungjawaban pelaksanaan VFA telah sesuai dengan pertanggungjawaban APBD.